Drivers for Asynchronous Patterns of Dust Accumulation in Central and Eastern Asia and in Greenland During the Last Glacial Maximum. Issue 5 (3rd March 2021) - Cheng, Liangqing; Song, Yougui; Wu, Yubin; Liu, Yonggang; Liu, Huifang; Chang, Hong; Zong, Xiulan; Kang, Shugang
Abstract: We collected 143 loess optically stimulated luminescence (OSL) ages between 10 ka and 30 ka from Central Asia (CA), and analyzed their probability density functions (PDFs). The PDFs show dust accumulation was greater during the late Last Glacial Maximum (LGM) (23–19 ka) than that during the early LGM (26.5–23 ka). The temporal variability of dust accumulation of CA loess is generally similar to that of Chinese Loess Plateau (CLP) loess, following precession. In contrast, dust accumulation in Greenland was stronger during the early LGM than that during the late LGM, following obliquity. Supported by numerical modeling experiments and our newly dating OSL ages, we conclude dust accumulation in CA and CLP during the LGM was controlled by Siberian High forced by precession, while dust accumulation in Greenland was closely related to both intensity of summer westerlies forced by obliquity, and to intensity of dust emissions at source forced by precession. Plain Language Summary: The dust accumulation in ice cores is often regarded as a direct record of the changing atmospheric dust loading reflecting the aridity of dust source regions. However, the underlying mechanism has not been well understood due to the lack of evidence from dust source regions. Here, we collected 143 optically stimulated luminescence (OSL) ages between 10 ka (ka means 1, 000 years) to 30 ka from Central Asia (CA) loess to build the probability density functions (PDFs). The PDFs revealed a stronger dust accumulation occurred during the late LGM than that during the early LGM. The variation pattern of dust accumulation of CA loess is generally similar to that of the Chinese Loess Plateau (CLP) loess, in phase with precession. In contrast, Greenland presents that stronger dust accumulation occurred during the early LGM rather than during the late LGM. The variation pattern of dust accumulation during the LGM in Greenland followed obliquity. Supported by numerical modeling experiment and our newly dating OSL ages, we assumed dust accumulation during the LGM in the CA and CLP was controlled by the Siberian High forced by precession. In contrast, dust accumulation in Greenland was closely related to both the intensity of summer westerlies forced by obliquity and dust emission driven by Siberian High forced by precession. Key Points: Asynchronous variations of dust accumulation at midlatitude Asia and Greenland during the Last Glacial Maximum (LGM) Dust accumulation in Asia during the LGM was controlled by Siberian High forced by precession Dust accumulation in Greenland is related to westerlies forced by obliquity and source dust emissions forced by precession